If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (y + 5)(y + -4w + -2) = 0 Reorder the terms: (5 + y)(y + -4w + -2) = 0 Reorder the terms: (5 + y)(-2 + -4w + y) = 0 Multiply (5 + y) * (-2 + -4w + y) (5(-2 + -4w + y) + y(-2 + -4w + y)) = 0 ((-2 * 5 + -4w * 5 + y * 5) + y(-2 + -4w + y)) = 0 ((-10 + -20w + 5y) + y(-2 + -4w + y)) = 0 (-10 + -20w + 5y + (-2 * y + -4w * y + y * y)) = 0 Reorder the terms: (-10 + -20w + 5y + (-4wy + -2y + y2)) = 0 (-10 + -20w + 5y + (-4wy + -2y + y2)) = 0 Reorder the terms: (-10 + -20w + -4wy + 5y + -2y + y2) = 0 Combine like terms: 5y + -2y = 3y (-10 + -20w + -4wy + 3y + y2) = 0 Solving -10 + -20w + -4wy + 3y + y2 = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '10' to each side of the equation. -10 + -20w + -4wy + 3y + 10 + y2 = 0 + 10 Reorder the terms: -10 + 10 + -20w + -4wy + 3y + y2 = 0 + 10 Combine like terms: -10 + 10 = 0 0 + -20w + -4wy + 3y + y2 = 0 + 10 -20w + -4wy + 3y + y2 = 0 + 10 Combine like terms: 0 + 10 = 10 -20w + -4wy + 3y + y2 = 10 Add '-3y' to each side of the equation. -20w + -4wy + 3y + -3y + y2 = 10 + -3y Combine like terms: 3y + -3y = 0 -20w + -4wy + 0 + y2 = 10 + -3y -20w + -4wy + y2 = 10 + -3y Add '-1y2' to each side of the equation. -20w + -4wy + y2 + -1y2 = 10 + -3y + -1y2 Combine like terms: y2 + -1y2 = 0 -20w + -4wy + 0 = 10 + -3y + -1y2 -20w + -4wy = 10 + -3y + -1y2 Reorder the terms: -10 + -20w + -4wy + 3y + y2 = 10 + -3y + -1y2 + -10 + 3y + y2 Reorder the terms: -10 + -20w + -4wy + 3y + y2 = 10 + -10 + -3y + 3y + -1y2 + y2 Combine like terms: 10 + -10 = 0 -10 + -20w + -4wy + 3y + y2 = 0 + -3y + 3y + -1y2 + y2 -10 + -20w + -4wy + 3y + y2 = -3y + 3y + -1y2 + y2 Combine like terms: -3y + 3y = 0 -10 + -20w + -4wy + 3y + y2 = 0 + -1y2 + y2 -10 + -20w + -4wy + 3y + y2 = -1y2 + y2 Combine like terms: -1y2 + y2 = 0 -10 + -20w + -4wy + 3y + y2 = 0 The solution to this equation could not be determined.
| .11y+.06(y+7000)=1440 | | X^3-7x^2= | | 6y-2=6 | | 3b-3=3(7-g) | | 5/7(k=5=-7 | | 4a-ax=3b+box | | m=9+3x-dx | | 8(2x-12)=27 | | 5x-(2r+8)=16 | | 1/4-5=-2 | | 5-2x=3x+7x+25 | | -2v^2-v+15v^2+16=0 | | 2k^2-16k=7 | | 4x^3y+8x^2+6x+5= | | 10(x+6)=-4(x-3) | | -4(8-3x)=-128 | | 21=-7/6*u | | 7g+(-89)=-33 | | 3x-7+11=5x+10 | | 11n+1=1 | | 3x-7+11=5+10 | | 5x-2(5+4x)=3+1x-8 | | 3x-2x=7x+x | | 4(7x+9)+7=28x+43 | | 2(7x-9)=x+9 | | 3y(5-11)y=3 | | 0.20(y-8)+0.06y=0.16y-0.01(60) | | 98=7(-4n+6) | | 3x^3y+5xz-4y+x-z+9= | | 2k^2=50 | | 5(5-f)=75 | | 4x+12=-6x-18 |